TCL1 oncogene expression in AIDS-related lymphomas and lymphoid tissues - Teitell, Michael (The National Academy of Sciences, 1999)
AIDS-related non-Hodgkin’s lymphoma (AIDS NHL) comprises a diverse and heterogeneous group of high-grade B cell tumors. Certain classes of AIDS NHL are associated with alterations in oncogenes or tumor-suppressor genes or infections by oncogenic herpesviruses. However, the clinically significant class of AIDS NHL designated immunoblastic lymphoma plasmacytoid (AIDS IBLP) lacks any consistent genetic alterations. We identified the TCL1 oncogene from a set of AIDS IBLP-associated cDNA fragments generated by subtractive hybridization with non-AIDS IBLP. Aberrant TCL1 expression has been implicated in T cell leukemia/lymphoma development, and its expression also has been seen in many established B cell tumor lines. However, TCL1 expression has not been reported in AIDS NHL. We find that TCL1 is expressed in the majority of AIDS IBLP tumors examined. TCL1 protein expression is restricted to tumor cells in AIDS IBLP tissue samples analyzed with immunohistochemical staining. Hyperplastic lymph node and tonsil also exhibit strong TCL1 protein expression in mantle zone B cells and in rare interfollicular zone cells, whereas follicle-center B cells (centroblasts and centrocytes) show weaker expression. These results establish TCL1 as the most prevalent of all of the surveyed oncogenes associated with AIDS IBLP. They also indicate that abundant TCL1 expression in quiescent mantle zone B cells is down-regulated in activated germinal center follicular B cells in parallel to the known expression pattern of BCL-2. High-level expression in nonproliferating B cells suggests that TCL1 may function in protecting naïve preactivated B cells from apoptosis.